2
$\begingroup$

The zeta function is defined as: $$ \zeta (x) = \sum\limits_{n=1}^{\infty} \frac {1}{n^x} $$

Does an integral of this function exist? If it does then what would it be?

More information about zeta function can be found here .

$\endgroup$
  • 4
    $\begingroup$ If you are happy with a sum you can put $\frac{1}{n^x} = e^{-ln(n)x}$ and integrate $\endgroup$ – Paul Feb 12 at 12:48
  • 1
    $\begingroup$ This is my mathematica code for the integrated Euler Maclaurin formula for the Riemann zeta function: pastebin.com/9wSSSmR4 You can skip the plot and go directly to the second part for faster execution. $\endgroup$ – Mats Granvik Feb 12 at 15:26
  • $\begingroup$ What do you mean precisely by exist ? $\endgroup$ – Yves Daoust Feb 13 at 8:44
3
$\begingroup$

[Rough Calculation] You may take it as an answer. I have been calculating the integration in the usual way, assuming $x$ to be real. $C$ is arbitrary constant.

$\displaystyle \int \zeta(x)dx=x-(\frac{1}{2^x\log 2}+\frac{1}{3^x\log 3}+\dots)+C$

Now, I claim that the infinite sum converges.

Since, for all $n>1$ and $x>1$ we have $\displaystyle\frac{1}{n^x}>\frac{1}{n^x\log n}$ summing over $n=2$ to $\infty$ we get,

$$\zeta(x)-1>\sum_{n=2}^\infty\frac{1}{n^x\log n}$$ [I have not used weak inequality as I have not worked on the fact that when they will be equal]

The convergence is followed by the comparison test. As an overview we can say, $$\int\zeta(x)dx>x-1+\zeta(x)$$

Hope this works.

$\endgroup$
1
$\begingroup$

Okay I think I may have a solution, though it isn't pretty.

We can write $ \zeta (x) $ as:

$$ \sum_{n=1}^{\infty}{\frac {1}{n^x}}= \sum_{n=1}^{\infty}{e^{-x \ln (n)}} $$ The expansion of $e^x$ is: $$ e^x=\sum_{k=0}^\infty \frac {x^k}{k!}$$ Similarly the expansion of ${e^{-x \ln (n)}}$ is: $$ \sum_{n=1}^{\infty}{\frac {1}{n^x}}=\sum_{n=1}^{\infty}{e^{-x \ln (n)}}=\sum_{n=1}^{\infty} \left(\sum_{k=0}^\infty \left( \frac {(-x)^k(\ln (n))^k}{k!} \right) \right) $$

Integrating the expression: $$\int \left(\sum_{n=1}^{\infty} \left(\sum_{k=0}^\infty \left( \frac {(-x)^k(\ln (n))^k}{k!} \right) \right)\right)dx= \sum_{n=1}^{\infty} \left(\sum_{k=0}^\infty \left( \frac {(-1)^k(x)^{k+1}(\ln (n))^k}{(k+1)k!} \right) \right)$$

$$\therefore~ \int\zeta (x)dx=\int \left (\sum_{n=1}^{\infty}{\frac {1}{n^x}} \right) dx= \sum_{n=1}^{\infty} \left(\sum_{k=0}^\infty \left( \frac {(-1)^k(x)^{k+1}(\ln (n))^k}{(k+1)k!} \right) \right)$$

$\endgroup$
  • $\begingroup$ Why to expand $e^{-x \log n}$? You can compute the integral directly according to Paul's comment: $$ \int e^{-x \log n} \,dx = -\dfrac{e^{-x \log n}}{\log n}+c, $$ for $n > 1$. $\endgroup$ – Alex Silva Feb 13 at 9:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.